RGD-based self-assembling nanodrugs for improved tumor therapy - Wang, Bin; Tang, Dongmei; Cui, Jianqiao; Jiang, Hongfei; Yu, Jing; Guo, Zhu (Frontiers in Pharmacology, 2024)
RGD-based self-assembling nanodrugs are a promising advancement in targeted cancer therapy, combining the specificity of RGD peptides with the benefits of nanotechnology. These nanodrugs enhance tumor targeting and cellular uptake while reducing off-target effects. RGD peptides facilitate the self-assembly of stable nanostructures, ensuring efficient drug delivery.Despite their potential, challenges such as immunogenicity, stability, tumor heterogeneity, and manufacturing scalability need to be addressed. Future research should focus on improving biocompatibility, advanced targeting strategies, personalized medicine approaches, and innovative manufacturing techniques. Overcoming these challenges will pave the way for the successful clinical translation of RGD-based nanodrugs, offering more effective and safer cancer treatments.